KONSEP POLA ASUH GRANDPARENTING TERHADAP SIKAP DAN PRESTASI ANAK SERTA PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI DAMPAK NEGATIFNYA - Walidatul Mustaghfirah; Abdulloh Hamid; Irfan Tamwifi (Raudhah - Proud To Be Professional, 2022)
The aim of this research is to find out the form of parenting used in grandparenting parenting at UPT SDN 378 Gresik, to find out the impact of the form of parenting used, and to find out the efforts made by PAI UPT SDN 37 Gresik teachers in overcoming the negative impacts of grandparenting parenting. The research method used is a descriptive-qualitative research method with a case study type. The data collection methods are observation, interviews, and documentation. The data was analysed using Miles, Huberman, and Saldana. Data analysis by testing the validity of the data in the form of triangulation of sources, time, and techniques. The results of the research are: 1) The form of parenting used by grandparents is a form of permissive and democratic parenting. 2) The impact of grandparenting depends on the parenting style used by grandparents. Not all children who experience grandparenting have poor performance and bad attitudes. 3) The efforts made by PAI teachers are to teach Islamic values, provide psychological support and counselling, teach children to obey their parents, and provide support and morals to their grandparents.